Identification and Avoidance of Malicious Nodes by using Certificate Revocation Method - Vamshi krishna, H.; Swain, Gandharba (International Journal of Engineering and Technology, 2018)
There are a large number of applications of ad-hoc networks (i) military, (ii) Disaster rescue, (iii) Medical etc.Â But the security of the data during transfer is a major concern. This paper proposes a technique for identifying and preventing the malicious nodes to be in a path from sender to receiver, known as certificate revocation method. Here certificate authority Scheme (CAS) is responsible for the issue of the certificates for these nodes. The CAS maintains two sets of lists â€“ a warning list and a blocked list. The node is added to a warning list if any of the neighbor nodes raises a suspension about a node. Both the accuser and the accused are added to this list. The node is transferred to blocked list when the corruption in the node is confirmed. A node from the blocked list is never added to the network again. This process is termed as cluster-based certificate revocation scheme (CBCRS). The priority of this technique is not the detection of the corrupted node but the removal of the corrupted node from the network. Experimental results reveal that this protocol is free from vulnerabilities. Â Â